Особенности строения мышц предплечья крота обыкновенного (Talpa europaea L.) - Бегека, А.Д. (Вестник зоологии, 1971)
In Talpa europaea L. in connection with the adaptation of thoracic limbs to digging the long digital muscles strengthened and carpus and hand muscles relaxed. M. flexor digitorum profundus is presented by connective tissue cord; m. palmaris longus inserts on praepollex and postminimus; m. abductor pollicis longus is fixed on the low end of the first carpus bone and on the inner surface of the first phalanx. Parallel with this in Talpa europaea L. m. extensor carpi radialis longus, m. extensor carpi ulnaris and m. flexor carpi ulnaris are absent and m. flexor carpi radialis is rudimentary.